An Assessment of an antioxidative status in patients with multiple sclerosis using standard biochemical analyzes - Andjelić, Tamara; Stevanović, Ivana; Mijušković, Mirjana; Dejanović, Bratislav; Ninković, Milica (Journal of Medical Biochemistry, 2025)
Background: The aim of the study was the assessment of antioxidative status using standard biochemical analyzes in multiple sclerosis patients during relapse and remission. Also, to evaluate the effects of gender, drug modified treatment and clinical characteristics of the multiple sclerosis on analyzed antioxidants. Methods: The study consisted of 178 relapse remitting multiple sclerosis patients (61 relapse/117 remission), 93 females and 85 males, mean age of 40.9 ± 9.8 age (average age of 40.9) and 80 matched healthy controls. Ongoing drug modified-treatment received 132 patients. The serum levels of uric acid, total bilirubin, albumin, and transferrin were analyzed in both patients and controls. Extended Disability Status Scale (EDSS), disease duration and annual relapse rate were used as a clinical characteristics of multiple sclerosis. Results: The antioxidant status was decreased in multiple sclerosis patients compared to controls. There was no statistically significant difference in antioxidant levels between relapse and remission. Women had less favorable antioxidative defense than men, with lower uric acid, total bilirubin and albumin. Negative correlations were found between disease duration and uric acid, and between annual relapse rate and total bilirubin. Use of disease-modifying therapy increased albumin levels. Conclusions: The use of standard biochemical analyzes as an antioxidant tool in patients with multiple sclerosis was evidenced in this study. The gender and clinical characteristics both affected antioxidant status, and highlighted the need for personalized complementary adds on antioxidative therapy in multiple sclerosis.